2018
DOI: 10.5539/gjhs.v10n10p65
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Determinants of Unintended Pregnancies Among Women in Abakaliki, Southeast Nigeria

Abstract: BACKGROUND: Unintended pregnancy is a major social and public health problem affecting women within the reproductive age group. It jeopardizes women’s sexual and reproductive health and may pose a threat to the achievement of Sustainable Development Goal 3. Objective: To determine the prevalence and determinants of unintended pregnancy in Abakaliki, Southeast Nigeria. METHODS: A semi-structured questionnaire was used for a cross-sectional survey of antenatal clinic attendees at the Feder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The prevalence of unintended pregnancy determined in this study is consistent with 33% reported for the African continent (Sedgh et al, 2014) but moderately lower than the prevalence 40% and 43.8% reported by Nyarko in Ghana (Nyarko, 2019) and Lawani et al in Nigeria (Lawani et al, 2018) respectively. The wide variations in the prevalence of unintended pregnancy determined in our study and the national figure reported by Nyarko relates to the different contexts of the two studies with the latter being a secondary analysis of countrywide national survey.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of unintended pregnancy determined in this study is consistent with 33% reported for the African continent (Sedgh et al, 2014) but moderately lower than the prevalence 40% and 43.8% reported by Nyarko in Ghana (Nyarko, 2019) and Lawani et al in Nigeria (Lawani et al, 2018) respectively. The wide variations in the prevalence of unintended pregnancy determined in our study and the national figure reported by Nyarko relates to the different contexts of the two studies with the latter being a secondary analysis of countrywide national survey.…”
Section: Discussionsupporting
confidence: 88%
“…Analysis of this study revealed that women living in urban areas had fewer chances to have ill time pregnancies than those residing in rural areas. 24 This could be due to poverty, limited availability of health services, and poor utilization of health care facilities, and ignorance. 25 We have found a significant relationship among age at first marriage with mistimed and not wanted pregnancy in India.…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, the cross-sectional study by Kassahun et al [8] reported a lower overall prevalence of unintended pregnancy (29.7%) among pregnant women attending antenatal care in Maichew Town, Tigray region, Northern Ethiopia. In Nigeria, the studies of Lamina [11] and Lawani et al [9] reported an unintended pregnancy prevalence of 35.9% and 43.8% among women in Ogun state and Abakiliki, respectively. However, a descriptive cross-sectional, questionnaire-based survey conducted among 254 pregnant women attending the antenatal clinic at the University of Abuja Teaching Hospital, Gwagwalada, Abuja by Agida et al [1] reported a 16% prevalence of unintended pregnancy.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the odds of unintended pregnancy in the study were 38.6 times (AOR = 38.6, 95% CI 10.07, 148.01) as high among women who were single compared to married women. Congruently, a cross-sectional study conducted in 2015 among 185 antenatal clinic attendees by Lawani et al [9] in Federal Teaching Hospital, Abakaliki, showed that the highest percentage (75%) of unintended pregnancies occurred in women within 45 -49 years age group followed by those within 15 -19 years age group (71.4%). The women within the 20 -24 years age group had the lowest percentage, 30.8% of unintended pregnancies.…”
Section: Introductionmentioning
confidence: 99%